A Study on the Use of Real Cases in Short Videos for Lung Cancer Public Awareness and Users' Willingness to Seek Relevant Health Information (The Journal of Medicine, Humanity and Media, 2025)
This study aims to explore the impact of real case presentations in medical and health science popularization short videos on users' willingness to seek health information. With the popularity of social media, short videos have become a key channel for the public to obtain health information. This study analyzed how different levels of display of real cases in short videos affect users' willingness to seek health information through perceived threats and perceived efficacy through experimental design. The study used the Simplified Disease Perception Questionnaire (BIPQ), the Fear of Disease Progression Simplified Scale (FoP-Q-SF), and the General Self Efficacy Scale (GSES) for measurement. The results showed that the degree of displaying real cases significantly increased users' willingness to seek health information. Perceived threat and perceived efficacy play a mediating role between short video content and user willingness. The study emphasizes the importance of using real cases in health education, providing strategies for enhancing public health awareness and behavior change. The research is limited by the sample size and does not cover all influencing factors. Future studies need to expand the sample size and explore in depth the dissemination effects of different health information.
Keywords: Lung Cancer Science Popularization Short Videos; Real Case Studies; Information Seeking; Perceived Threat; Perceived Efficacy